2012
DOI: 10.1590/s0102-09352012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Morfometria testicular de cabritos alimentados com óleo de licuri (Syagrus coronata)

Abstract: RESUMODeterminou-se o desenvolvimento testicular de caprinos pré-púberes alimentados com óleo de licuri (Syagrus coronata) na dieta. Foram utilizados 19 cabritos ¾ Boer, recém-desmamados, com média de idade de três meses. Os animais, submetidos a um período de 75 dias de confinamento, receberam alimentação composta por: farelo de milho, farelo de soja, feno picado de tifton 85 e de óleo de licuri com base na matéria seca. Os animais foram distribuídos em quatro grupos: sem lipídio adicional (n= 5); com 1,5% de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The addition of LIK oil in the diet of goats up to 4.5% did not cause significant changes in the carcass [204] and the milk's physicochemical properties [205]. Another study found that up to 4.5% LIK oil in the diet of prepubertal male goats did not alter testicular development based on testicular biometry and morphometry [206]. These findings indicated that LIK oil could be an alternative lipid source for animal nutrition in the semi-arid regions of northeastern Brazil [204,205].…”
Section: Biological Effects Reported For Aptfosmentioning
confidence: 96%
“…The addition of LIK oil in the diet of goats up to 4.5% did not cause significant changes in the carcass [204] and the milk's physicochemical properties [205]. Another study found that up to 4.5% LIK oil in the diet of prepubertal male goats did not alter testicular development based on testicular biometry and morphometry [206]. These findings indicated that LIK oil could be an alternative lipid source for animal nutrition in the semi-arid regions of northeastern Brazil [204,205].…”
Section: Biological Effects Reported For Aptfosmentioning
confidence: 96%